Meningkatkan Kinerja Guru dalam Pengelolaan Pembelajaran Melalui Supervisi Akademik dan Coaching - Yulita Suarni (Dinasti Research, 2023)
Learning at SMA Negeri 1 Painan, especially regarding the planning and implementation of learning. To overcome this, school action research was carried out by school supervisors as supervising supervisors in the form of optimizing academic supervision and coaching in the January-July 2022 semester. This research is included in the type of action research with 4 stages of activity, planning, implementation, observation and reflection carried out during 2 cycles. The data needed in the research is netted through observation sheets and questionnaires. Data processing is carried out using the percentage formula, and data analysis is carried out quantitatively and qualitatively using tables and graphs. The results of the study show that through academic supervision there has been an increase in teacher performance in managing learning with regard to: a) Availability of teacher lesson plans components as much as 79.50% in cycle 1 increased to 100% at the end of cycle 2. b) average teacher lesson plan component quality being in the very good category increased from 42.19% in cycle 1 to 75% at the end of cycle 2, and the rest were in the good category. c) The quality of teacher learning increased from 31.3% which was in the very good category to 35% at the end cycle 2.